Japan-China 2008 Agreement: Common-Pool Resource Governance Problem - Rafyoga Jehan Pratama Irsadanar; Kan Kimura (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2021)
This research aims to answer the reason behind the stalled progress of dispute settlement in East China Sea between Japan and China, despite a high initial commitment to cooperate under